Endotoxin Exposure, Serum Vitamin D, Asthma and Wheeze Outcomes - Mendy, Angelico (Respir Med, 2016)
BACKGROUND: Endotoxin has been shown to induce neutrophilic asthma and wheeze after binding toll-like receptor 4 to produce pro-inflammatory cytokines. Animal models have demonstrated that vitamin D might inhibit lipopolysaccharide-induced cytokines. However, whether endotoxin exposure and serum vitamin D deficiency interact to affect asthma and wheeze in humans has never been investigated in an epidemiological study. METHODS: Joint associations of house dust endotoxin and vitamin D with asthma and wheeze were examined using logistic regression adjusted for covariates in 5,924 US participants of the National Health and Nutrition Examination Survey (NHANES). Interactions were assessed on the multiplicative as well as additive scale using the relative excess risk, the attributable portion due to additive interaction, and the synergy index. RESULTS: The median endotoxin concentration was 19.1 EU/mg. Prevalence of vitamin D inadequacy (20–30 ng/ml) and deficiency (<20 ng/ml) were respectively 42.9 and 33.4%. The combination of high endotoxin and low vitamin D was associated with current asthma (OR: 1.56, 1.09, 2.23), wheeze in the past 12 months (OR: 1.72, 95% CI: 1.10, 3.71), recurrent wheeze (OR: 1.97, 95% CI: 1.00, 4.00), asthma diagnosis or recurrent wheeze (OR: 1.88, 95% CI: 1.33, 2.66), and current asthma or recurrent wheeze (OR:1.81, 95% CI: 1.23, 2.68) when compared to low endotoxin and normal vitamin D. Though, the interactions between the exposures were not significant on the multiplicative or additive scale for any of the outcomes. CONCLUSIONS: Combination of high endotoxin exposure and low vitamin D increases the odds of asthma and wheeze, but the exposures do not interact or modify each other’s effect in the NHANES cohort.